Cloud Security Certification Technology Based on Fingerprint Recognition - Yafei Tang; Yunyong Zhang; Ni Zhang (Dianxin kexue)
As the guarantee of cloud security，user identity authentication is crucial to cloud computing.In this work，the requirements of security authentication in the current cloud service systems were analyzed.Considering the principle and the advantages of fingerprint recognition，a novel system based on fingerprint recognition was proposed for cloud security authentication.The architecture and workflow of the proposed system were investigated in depth to prevent the unauthorized access，achieving the secure access of user data for cloud services.